Circular economy in the tourism industry: mapping drivers and barriers through a systematic literature review - Almici, Alex; Bosetti, Luisa; Cassano, Raffaella; Fornasari, Tommaso; Gennari, Francesca (Piccola Impresa / Small Business, 2025)
Purpose. This study explores how the Circular Economy (CE) is conceptualized and implemented in the tourism sector, a service industry still marginally addressed in academic research on circular transitions. Design/methodology/approach. Through a systematic literature review and qualitative content analysis of 64 journal articles, the paper identifies drivers and barriers that influence the CE adoption. These factors are classified into three dimensions: governance, stakeholder relations, and innovation. Findings. While innovation and stakeholder relations are widely discussed in the literature, governance is significantly underexplored. Moreover, only few studies adopt a comprehensive perspective that integrates all three dimensions. Practical and social implications. From a managerial standpoint, the study provides insights for aligning internal capabilities with external enablers, especially for SMEs. Originality of the study. The paper offers an analytical lens for understanding CE practices in service-based industries and stresses the need for more holistic approaches.